(untitled) (Eurasian Research Bulletin, 2022)
Organometallic frameworks (MOFs) as a type of porous nanoparticle are promising candidates for immobilizing enzymes to increase their stability and reuse. However, most MOFSs cannot specifically immobilize enzymes and regenerate easily, which inevitably leads to serious high consumption and pollution of the environment. In this study, Renewable and magnetic MOFSs were first designed to specifically immobilize his-labeled enzymes from cell lysates without purification. Immobilized fig glucuronidase exhibited broader pH adaptability and temperature stability. The relative activity of immobilized bglucuronidase remained at 80% after eight cycles. It is important to note that after simple treatment, the immobilization capacity of the regenerated MOFSs, after simple treatment, was recovered by more than 90% in the first three times. Specific magnetic MOFSs have been proven to be an efficient and renewable platform for one-step immobilization and purification of His-labeled enzymes, demonstrating great potential in industrial applications of nanotechnology and biocatalysis